Determination of Dopamine by Dual Doped Graphene-Fe2O3 in Presence of Ascorbic Acid. Issue 14 (1st January 2015) - Yasmin, Sabina; Ahmed, Mohammad Shamsuddin; Jeon, Seungwon
Abstract : Both nitrogen and sulfur dual doped graphene supported Fe2 O3 (NSG-Fe2 O3 ) have been prepared by hydrothermal methods and subsequently utilized for the electrochemical determination of dopamine (DA) in presence of ascorbic acid (AA). The NSG-Fe2 O3 has been characterized via transmission electron microscopy (TEM) and X-ray photoelectron spectroscopic (XPS). The electrochemical detection of DA was measured through the cyclic voltammetry, differential pulse voltammetry, and amperometric techniques in a 0.1 M phosphate buffer solution (PBS) at pH 7.4. Interferences have been investigated in presence of AA, glucose, serotonin, N2 H4, and uric acid. The NSG–Fe2 O3 has shown good analytical performance for DA with comparatively better sensitivity (29.1 μA mM −1 ), long linear detection range (0.3–210 μM) and detection limit (0.035 μM) ( S/N = 3). The catalytic rate constant for DA detection has been calculated as 9.6 × 10 4 M −1 s −1 with a good diffusion coefficient of 3.5 × 10 −4 cm 2 s −1 . The electrooxidation of DA may enhances by fast proton acceptance and/or electron donation due to higher electron density for excess loan pair electron that provided from N and S dual-doped graphene sheets.